Adsorption Mechanism of Expanded Graphite for Oil and Phenyl Organic Molecules - PANG, XIU-YAN; LIN, RUI-NIAN (Asian Journal of Chemistry, 2010)
Expanded graphite shows higher adsorption capacity for oils (e.g., salad oil and thermal oil) than for phenyl organic molecules (e.g., phenol, benzoic acid, benzene sulfonic acid, p-methylbenzene sulfonic acid). To illustrate their different adsorption mechanism, adsorption capacities of expanded graphite for these pollutants are firstly detected. And then stepwise adsorption for oils is carried out with expanded graphite which has been saturated first by phenyl organic molecules. Then the difference between stepwise adsorbance of oil is checked with deviation analysis. Scanning electronic microscopy (SEM) analysis is used to show structure difference of expanded graphite adsorbed different adsorbates. It is testified the adsorption isotherms of phenyl organic molecules on expanded graphite are all type II. Deviation analysis for stepwise adsorbances of oil shows no statistical significance. Expanded graphite saturated first by phenyl organic molecules, still has an average adsorption capacity of 79 g/g for salad oil or thermal oil and it does not change with the initial phenyl organic molecules concentration. Scanning electronic microscopy photos illustrate the adsorption of oil on expanded graphite is mainly filling. In the adsorption of phenyl organic molecules, there is severe breakage of the V-type pore and shrinkage of the particles.